Cutaneous manifestations and associated systemic findings of patients with zika infections - Charussri Leeyaphan (2020)
© 2020 Faculty of Medicine Siriraj Hospital, Mahidol University. Objective: This retrospective study explored the clinical characteristics and laboratory results of ZIKV infections, and compared them with those of other viral exanthems. Methods: The medical records of patients presenting with maculopapular viral exanthems between January 2017 and December 2018 were reviewed. The patients were divided into 2 two groups: ZIKV infections (confirmed by urine RT-PCR testing for ZIKV), and other viral exanthems. The clinical characteristics and laboratory results of complete blood counts of the two groups were compared. Results: In all, 104 viral-exanthem patients were reviewed, with 35 patients diagnosed with a ZIKV infection (33.7%) and 69 with other viral exanthems (66.3%). The mean age of the ZIKV-infected patients was significantly higher than that of the other-viral-exanthem group (43.6 vs 36.2 years; p-value = 0.005). A multivariate analysis revealed that the incidences of a family/close contact cluster, conjunctivitis, and myalgia were significantly associated with ZIKV infections. However, there were no significant associations between the laboratory results of the ZIKV and other-viral-exanthem groups. Conclusion: The ZIKV infection exhibits a prominent pattern recognition, including a family/close contact cluster, conjunctivitis, and myalgia, that can be used to distinguish it from other exanthematous viral diseases.